Demographic Situation in Goričko Landscape Park from the Perspectives of Prekmurje and Slovenia - Malačič, Janez (Anali PAZU, 2022)
The demographic development in the Goričko landscape park is determined by the modern demographic regime prevailing in advanced countries in Europe. Due to statistical problems the population of the park is analyzed on the basis of the data for 11 communes which partly or completely occupy the territory of the park. The share of the estimated population in the park at the beginning of the year 2010 was 22.7 % of the Pomurska region population and 1.3 % of the population of Slovenia. Intensive population ageing is the most important demographic characteristic of the population in the park. It is caused mainly by low fertility and emigration of younger people. In 2009, mortality was higher than fertility in all communes included in the analysis but one. The demographic situation in the park is better in the western side closer to the border with more developed Austria in comparison with the eastern parts which border with less developed Hungary. Generally, the demographic situation in Goričko landscape park is determined by low level of economic development. The economic activity in the park is dominated by small farming and very low development of manufacturing and tertiary activity.